Silver(I) Oxide‐/DBU‐Promoted Synthesis of Dihydrofuran Units through Allenyl Silver Formation. Issue 72 (1st December 2020) - Yu, Bao; Perfetto, Anna; Allievi, Luca; Dhambri, Sabrina; Rager, Marie‐Noelle; Selkti, Mohamed; Ciofini, Ilaria; Lannou, Marie‐Isabelle; Sorin, Geoffroy
Abstract: A formal [3+2] cyclization mediated by silver(I) oxide and 1, 8‐diazabicyclo[5.4.0]undec‐7‐ene (DBU) is described herein. Through a broad variety of carbonyl compounds, this system can promote cyclization reactions with high yield (up to 85 %) and diastereoselectivity (up to 95:5) for a straightforward access to complex and congested dihydrofuran derivatives in one step under mild conditions. Based on DFT studies, the proposed mechanism would involve an allenyl silver intermediate. Abstract : An easy way to complex : An unprecedented isomerization/allenyl silver formation/[3+2] cyclization promoted by a combination of silver salts and base is presented. The reaction, which is broad in scope, allows the straightforward and diastereoselective (up to 95:5 dr ) synthesis of complex dihydrofuran frameworks under mild conditions from easily accessible substrates.